The endocannabinoid system and drug-associated contextual memories. Issue 2 (8th February 2021) - Asth, Laila; Santos, Aline C.; Moreira, Fabrício A.
Abstract : Drug abuse and addiction can be initiated and reinstated by contextual stimuli previously paired with the drug use. The influence exerted by the context on drug-seeking behaviour can be modelled in experimental animals with place-conditioning protocols. Here, we review the effects of cannabinoids in place conditioning and the therapeutic potential of the endocannabinoid system for interfering with drug-related memories. The phytocannabinoid Δ 9 -tetrahydrocannabinol (THC) tends to induce conditioned place preference (CPP) at low doses and conditioned place aversion at high doses; cannabidiol is devoid of any effect, yet it inhibits CPP induced by some drugs. Synthetic CB1 receptor agonists tend to recapitulate the biphasic profile observed with THC, whereas selective antagonists/inverse agonists inhibit CPP induced by cocaine, nicotine, alcohol and opioids. However, their therapeutic use is limited by potential psychiatric side effects. The CB2 receptor has also attracted attention, because selective CB2 receptor agonists inhibit cocaine-induced CPP. Inhibitors of endocannabinoid membrane transport and hydrolysis yield mixed results. In targeting the endocannabinoid system for developing new treatments for drug addiction, future research should focus on 'neutral' CB1 receptor antagonists and CB2 receptor agonists. Such compounds may offer a well-tolerated pharmacological profile and curb addiction by preventing drug-seeking triggered by conditioned contextual cues.